2016
DOI: 10.1097/md.0000000000004530
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative risk factors for in-hospital mortality after emergency gastrointestinal surgery

Abstract: Few studies have evaluated the risk factors for in-hospital mortality in critically ill surgical patients who have undergone emergency gastrointestinal (GI) surgery. The aim of this study was to identify the risk factors associated with in-hospital mortality in critically ill surgical patients after emergency GI surgery.The medical records of 362 critically ill surgical patients who underwent emergency GI surgery, admitted to intensive care unit between January 2007 and December 2011, were reviewed retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 27 publications
4
33
1
1
Order By: Relevance
“…19,29 Haematology Increased mortality was observed in patients with reduced platelet levels in two studies, inclusive of a large study by Peponis et al 26,29 Likewise, low haemoglobin levels were associated with an increased mortality in one small study (Table S5). 27 Deranged white cell count (WCC) is associated with increased mortality in three studies, inclusive of the two largest studies, by Al-Temimi et al and Peponis et al 19,24,29 Two smaller studies did not show any significant difference in mortality with deranged WCC (Table S5). 25,27 Blood glucose level Two studies investigated the influence of blood glucose level (BGL) on mortality after an EL.…”
Section: Serum Albuminmentioning
confidence: 98%
See 3 more Smart Citations
“…19,29 Haematology Increased mortality was observed in patients with reduced platelet levels in two studies, inclusive of a large study by Peponis et al 26,29 Likewise, low haemoglobin levels were associated with an increased mortality in one small study (Table S5). 27 Deranged white cell count (WCC) is associated with increased mortality in three studies, inclusive of the two largest studies, by Al-Temimi et al and Peponis et al 19,24,29 Two smaller studies did not show any significant difference in mortality with deranged WCC (Table S5). 25,27 Blood glucose level Two studies investigated the influence of blood glucose level (BGL) on mortality after an EL.…”
Section: Serum Albuminmentioning
confidence: 98%
“…27 Deranged white cell count (WCC) is associated with increased mortality in three studies, inclusive of the two largest studies, by Al-Temimi et al and Peponis et al 19,24,29 Two smaller studies did not show any significant difference in mortality with deranged WCC (Table S5). 25,27 Blood glucose level Two studies investigated the influence of blood glucose level (BGL) on mortality after an EL. 18,20 One small study, by Awad et al, demonstrated an increase in the 30-day mortality with an increasing BGL, although this result was not statistically significant (Table S5).…”
Section: Serum Albuminmentioning
confidence: 98%
See 2 more Smart Citations
“…23 To conclude, proximal bowel is injured much more commonly than distal bowel by perforations. Gastrointestinal perforations show increased morbidity in patients with associated risk factors including smoking, chronic NSAID intake and alcohol abuse.…”
Section: Discussionmentioning
confidence: 99%